A study of the effect of globalization on society - Mannu Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
Ahuja, Ram (2001), Research Methods, Rawat Publication. AntonicoFermano da costa, (2002), Urban cultural identities in a time of globalization. Barran, R D and Norris, G M, (1976), Sexual divisions and the dual Labour Markets in Barker and Allen. Bernard J, (1976), The future of marriage, Penguin Books, Harmandsworth. Bhagat Chetan, (2004), Five point someone, Rupa & Co. Dunklin, A, (2005), Globalization: a portrait of exploitation, inequality and limits. Lee Lisa, (2005), Young people and the Internet-From theory to practice. Linda McDowell, (2004), Global change, local lives, youth and societies. Rantanen, T, (2005), the media and globalization, London Sage. Rohweder Die Jan, (2006), Globalization and its critics. Triandis, H C, (2006), Cultural aspects of Globalization, Journal of International management, pp 208-17. Turner Bryans, (2003), Cultural and cross cultural perspective on parent- youth relations. Turner Elen, (2012), the Gender anxiety and contemporary Indian popular fiction. Water, M, (1995), Globalization, New Delhi, Prentice Hall of India.